Pengujian Program Mindfulness Singkat untuk Menurunkan Penunda-nundaan Skripsi pada Mahasiswa - Cahyo Setiadi Ramadhan; Nida Ul Hasanat (Faculty of Psychology, Universitas Gadjah Mada, 2016)
The aim of this study was to test the ability of brief mindfulness-based program on reducing academic procrastination. Hypotheses of this study was that there is difference of declining level of procrastination between participants of program (i.e. experimental group) compared to non-participants (i.e. control group). Students were recruited as participants of study (N = 21) and divided non-randomly into experimental group (n = 11) and control group (n = 10). For the ethics reason, control group treated as waiting-list. Academic procrastination level was measured by Tes Kegunaan Subjektif Skripsi (TKSS). Data analysis showed there was no significant difference in the TKSS score of experimental group and control group (U = 39; z = -1,127; nE = 11; nK = 10; p = 0,260). It was clear that brief mindfulness-based program cannot reduce academic procrastination in undergraduate thesis writing.